Clinical characteristics and predictive factors for mortality in coryneform bacteria bloodstream infection in hematological patients. Issue 3 (March 2017) - Kimura, Shun-ichi; Gomyo, Ayumi; Hayakawa, Jin; Akahoshi, Yu; Harada, Naonori; Ugai, Tomotaka; Komiya, Yusuke; Kameda, Kazuaki; Wada, Hidenori; Ishihara, Yuko; Kawamura, Koji; Sakamoto, Kana; et al.
Abstract: Background: We examined the clinical characteristics and predictive factors for mortality in coryneform bacteria bloodstream infection in hematological patients. Methods: We searched for hematological patients who had positive blood cultures for coryneform bacteria at our center between April 2007 and January 2016. Patients with definite bloodstream infections were included. We started species identification in April 2014. Results: Twenty of twenty-eight cases with a positive blood culture for coryneform bacteria were regarded as definite infections. Sixteen and two patients were allogeneic and autologous hematopoietic stem cell transplantation (HSCT) recipients, respectively. Corynebacterium striatum was identified in all nine of the cases tested and one patient was co-infected with Corynebacterium amycolatum . None of the patients died directly due to coryneform bacteria infection. The survival rates at 30, 60 and 180 days were 100%, 73.7% and 51.3%, respectively. Causes of mortality included progression of the underlying disease (n = 6), other infections (n = 4) and HSCT complications (n = 2). Mixed infection (hazard ratio (HR) 5.47, 95% confidence interval (CI) 1.30–23.0), renal impairment (HR 6.31, 95% CI 1.06–37.4) and absence of a central venous (CV) catheter at the onset (HR 6.39, 95% CI 1.04–39.45) were identified as predictive factors for mortality. Conclusion: Most of the coryneform bacteria bloodstream infections occurred in HSCT recipients. Contamination seemed to be less common when coryneform bacteria were detected in blood in hematological patients. Although coryneform bacteria bloodstream infection seemed to mostly be manageable, the prognosis was not desirable, particularly in patients with mixed infection, renal impairment and absence of a CV catheter.